2010
DOI: 10.1002/hep.23420
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Therapy With Peroxisome Proliferation-Activator Receptor-α Agonist Wy-14,643 Protects Murine Fatty Liver Against Ischemia–Reperfusion Injury

Abstract: Steatosis increases operative morbidity/mortality from ischemia-reperfusion injury (IRI);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…However, it has been shown that PPAR␣ agonist treatment decreases nonalcoholic steatohepatitis (NASH) development in wild-type mice fed a methionine choline-deficient diet 3,4 and apolipoprotein E2 knock-in (apoE2-KI) mice or foz/foz mice fed a high-fat diet. 5,6 Moreover, PPAR␣ is expressed in many cell types found in …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that PPAR␣ agonist treatment decreases nonalcoholic steatohepatitis (NASH) development in wild-type mice fed a methionine choline-deficient diet 3,4 and apolipoprotein E2 knock-in (apoE2-KI) mice or foz/foz mice fed a high-fat diet. 5,6 Moreover, PPAR␣ is expressed in many cell types found in …”
mentioning
confidence: 99%
“…However, it has been shown that PPAR␣ agonist treatment decreases nonalcoholic steatohepatitis (NASH) development in wild-type mice fed a methionine choline-deficient diet 3,4 and apolipoprotein E2 knock-in (apoE2-KI) mice or foz/foz mice fed a high-fat diet. 5,6 Moreover, PPAR␣ is expressed in many cell types found in the atherosclerotic lesion, such as macrophages, endothelial cells, and smooth muscle cells. 7 In vitro and in vivo studies have suggested that fibrates could exert antiatherogenic actions by improving lipid abnormalities or by modulating several steps of atherogenesis, such as decreasing inflammation and thrombosis, directly in the vascular wall.…”
mentioning
confidence: 99%
“…There are some studies showing the detrimental effects of PPARa deficiency or the protective effects of PPARa activation in hepatic ischemia/reperfusion injury models using both lean and steatotic livers [27][28][29][30]. Notably, these models in general produced a more severe injury than our transplantation model and the protection by PPARa likely related to down-regulation of the pro-inflammatory response.…”
Section: Discussionmentioning
confidence: 73%
“…Sosnowski P et al [8] observed an increase in both ALT activity and liver tissues free radicals level after hind limb IR in rats. Teoh NC et al [9] observed ALT levels release exacerbation 24hours after induced steatohepatitis or simple steatosis hepatic IR in foz/foz mice than wild-type littermates. Ikeda A et al [10] found serum ALT levels significantly less in rat pre-transplanted liver grafts preserved in the University of Wisconsin (UW) solution containing 5% CO (CO-UW solution) group for 21 hours, than preserved in the control UW group one in Lewis rats.…”
Section: Discussionmentioning
confidence: 99%